Losing the workers who need employment the most: how health and job quality affect involuntary retirement. (2nd October 2018) - Welsh, Jennifer; Strazdins, Lyndall; Charlesworth, Sara; Kulik, Carol T; D'Este, Catherine
ABSTRACT: Governments are encouraging workers to remain in employment beyond traditional retirement age. A tangible expression of this in Australia is the move to raise the Aged Pension access age from 65 to 67 by 2023. This policy assumes that the majority of workers will be able to extend their working lives. However, even at the age of 65, one-third of older workers have left their jobs involuntarily, with poor health an important reason for exit. Yet the significance of worker health for maintaining or limiting employment is not reflected in current policy architecture. This article draws on the Household Income and Labour Dynamics in Australia Survey and uses a prospective, longitudinal study design. Our analysis estimates the extent poor health limits working past 50 and the ways in which health-related risk are compounded by other forms of labour market disadvantage. We find that having a chronic health condition is associated with a five-fold increase in the risk of involuntary retirement from work. Moreover the overwhelming majority of those with a health condition will leave the labour market because of it. We also find evidence that labour market disadvantage linked to caregiving, occupation and job quality compounds health-related involuntary retirement.